DEVELOPMENT OF CONTEXTUAL E-MODULES IN MATHEMATICS LEARNING IN STATISTICS MATERIALS - Sugihandardji, Chumaedi; Setiowati, Sulis; Wardayani, Ari; Gunawan, Gunawan; Kusuma, Jaka Wijaya; Widiyastuti, Erni (Yayasan Education and Social Center, 2025)
Encouraging the use of the independent curriculum emphasizes flexibility and student-centered learning. The development of a contextual e-module provides a solution to facilitate relevant and interactive mathematics learning, particularly in statistics for eighth-grade students. This e-module is designed based on students' daily experiences, making the material easier to understand and promoting independent learning. The research method used is Research and Development (RD) with the 4D model (Define, Design, Develop, Disseminate). Validation results from the subject matter and media experts indicate that the contextual e-module in mathematics learning on statistics for eighth grade is valid. Practicality tests through teacher and student response questionnaires show highly practical results, with average scores of 3.6 and 3.5 on a maximum practicality scale of 4.0. In conclusion, the contextual e-module in mathematics learning on statistics for eighth grade has proven valid and practical for use in mathematics education and can serve as an effective and relevant learning resource tailored to students' current needs and conditions.